Üzüm Sapından Hazırlanan Aktif Karbon ile Sulu Çözeltilerden Ni(II)’nin Giderimi - Orhan, Ramazan; Erdem, Mehmet (Fırat University, 2017)
Bu çalışmada, üzüm sapından hazırlanan yeni bir aktif karbon ile sabit yataklı kolonda sulu çözeltilerden Ni(II) adsorpsiyonu incelendi. Ni(II) giderimi üzerine akış hızı, pH ve başlangıç metal konsantrasyonu gibi parametrelerinin etkisi araştırıldı. Aktif karbon üzerine Ni(II) adsorpsiyonunun pH’ya bağımlı olduğu bulundu. 20 mg/L başlangıç Ni(II) konsantrasyonu için 25ºC sıcaklıkta yapılan deneylerde; en yüksek giderim veriminin (% 92.3) pH 4 ve 2 mL/dk akış hızında elde edildiği tespit edilmiştir

In this study; the adsorption of Ni(II) from aqueous solution by a novel activated carbon prepared from grape stalk was investigated in a fixed-bed column. The effect of selected operating parameters such as flow rate, pH and initial metal concentration on the Ni(II) removal were studied. It has been determined that the adsorption of Ni(II) onto activated carbon is pH dependent. The maximum adsorption yield (92.35 %) was obtained by using the activated carbon at the conditions of pH 4, flow rate of 2 mL/min for the initial Ni(II) concentration of 20 mg/L at 25°C
Ni(II) Removal from Aqueous Solutions by Activated Carbon Prepared from Grape Stalk